Living with Betrayal - Henry, Martin (New blackfriars, 2010)
This article addresses the idea that, over the centuries, Christianity has survived only by betraying its own uncompromising ideals. It investigates how damaging this interpretation could be for Christianity, and suggests that Christianity's survival might paradoxically be a function of the very phenomenon that seems at first sight to undermine it.